A Comparative Study of Science Education Students’ Academic Competence Under Benchmark Minimum Academic Standard and Core Curriculum Minimum Academic Standard Curricula in the University of Lagos, Nigeria - Oladipo, Juliana Adenike; Ojo, Omolabake T.; Awofala, Adeneye O.A. (NIU Journal of Humanities; Vol 11 No 1 (2026): NIU Journal of Humanities, Vol. 11 No. 1, March 2026DO - 10.58709/niujhu.v11i1.2463, 2026)
Curriculum reform remains a central strategy for enhancing the quality and relevance of university education, particularly in teacher education, where curriculum effectiveness has a direct impact on future classroom practice. In Nigeria, the transition from the Benchmark Minimum Academic Standards (BMAS) to the Core Curriculum Minimum Academic Standards (CCMAS) represents a shift from content-driven instruction to an outcome-based, competency-oriented framework. However, empirical evidence comparing the effects of these two curriculum frameworks on students’ academic competence remains limited. This study, therefore, conducted a comparative analysis of science education students’ academic competence under the BMAS and CCMAS curricula at the University of Lagos, Nigeria. Adopting a comparative descriptive research design with a quantitative approach, the study involved 328 undergraduate science education students, comprising 164 students trained under BMAS and 164 students trained under CCMAS. Data were collected using the Education Students’ Curriculum Experience Questionnaire, a Pedagogical Knowledge Test, and students’ academic achievement records. Descriptive statistics, independent samples t -tests, multivariate analysis of variance (MANOVA), and effect size estimates were employed for data analysis. Findings revealed that students trained under CCMAS significantly outperformed their BMAS counterparts in academic engagement, learning motivation, teaching confidence, academic achievement, and pedagogical knowledge, with effect sizes ranging from moderate to large. The MANOVA results further indicated a significant multivariate effect of curriculum framework type on students’ overall academic competence. These findings suggest that the outcome-based, student-centred orientation of CCMAS more effectively promotes cognitive, affective, and professional learning outcomes than the traditional content-focused BMAS. The study concludes that CCMAS represents a substantive improvement in science teacher education and recommends sustained institutional support, lecturer capacity development, and continuous evaluation to maximise the benefits of curriculum reform in Nigerian universities. Keywords: Curriculum Reform; BMAS; CCMAS; Academic Competence; Science Education; Teacher Education; Nigeria